Intensive silviculture enhances biomass accumulation and tree diversity recovery in tropical forest restoration - Brancalion, Pedro H. S.; Campoe, Otavio [UNESP]; Teixeira Mendes, Joao Carlos; Noel, Camilla; Moreira, Gabriela G.; van Melis, Juliano; Stape, Jose Luiz [UNESP]; Guillemot, Joannes (Wiley-Blackwell, 2019)
Maximizing initial aboveground woody biomass (AGB) accumulation in order to obtain early payments for carbon stocking is essential for the financial viability of reforestation programs fostered by climate mitigation efforts. Intensive silviculture, i.e., silviculture traditionally used in commercial forestry to maximize productivity and gains, has recently been advocated as a promising approach to enhance AGB accumulation in restoration plantations. However, this approach may hamper natural forest regeneration and ecological succession due to high competition between colonizing plants and planted trees. We investigated the impacts of different silvicultural treatments applied to restoration plantations with 20 native tree species on AGB accumulation and spontaneous regeneration of native woody species in an experiment set up in the Atlantic Forest of Brazil. Intensive silviculture demonstrated a remarkable potential to enhance AGB accumulation in restoration plantations by increasing up to three times the AGB of tree stands (from similar to 25 to 75 Mg/ha in the 12th year). Intensive fertilization/weed control enhanced AGB accumulation, while higher tree density and the proportion of pioneers did not have a significant effect on AGB over the time. In spite of higher costs (cost increase of 13-19%), the cost-effectiveness for AGB accumulation of intensive silviculture was comparable to that of traditional silviculture applied to restoration (US$50-100/Mg AGB for 3 x 2 m spacing). Contrary to our expectations, we did not find a trade-off between AGB accumulation by planted trees and the spontaneous regeneration of tree species, since intensive silviculture enhanced the regeneration of both planted (total of 12 species) and colonizing woody species (total of 30 species) in the plantation understory. Specifically, a strong association was found between AGB stocks and the abundance and richness of colonizing species, a vast majority of which (90% of species and 95% of individuals) were dispersed by animals. We report a case of positive correlation between AGB stocking and woody species regeneration in the restoration of the Atlantic Forest. Fostering the establishment and maintenance of restoration tree plantations can, in some cases, be a win-win strategy for climate mitigation and biodiversity conservation in human-modified tropical landscapes.
Keywords: Atlantic Forest; carbon accumulation; cost-effective silviculture; natural regeneration; restoration plantations; silvicultural management; tropical forestry